Proteomic analysis of spinal cord tissue in a rat model of cancer-induced bone pain - Yang, Heyu; Wu, Ji; Zhen, Shuqing; Hu, Yindi; Li, Dai; Xie, Min; Zhu, Haili (Frontiers in Molecular Neuroscience, 2022)
Cancer-induced bone pain (CIBP) is a moderate to severe pain, and seriously affects patients’ quality of life. Spinal cord plays critical roles in pain generation and maintenance. Identifying differentially expressed proteins (DEPs) in spinal cord is essential to elucidate the mechanisms of cancer pain. In the current study, CIBP rat model was established by the intratibial inoculation of MRMT-1 cells. CIBP rats exhibited bone damage, spontaneous pain, mechanical hyperalgesia, and impaired motor ability. The Positron emission tomography (PET) scan showed an hypermetabolism and functional abnormality on spinal cord of CIBP rats. Transmission electron microscopy (TEM) data revealed an increase of synaptic vesicles density in active zone and a disruption of mitochondrial structure in spinal cord of CIBP rats. To investigate key proteins contributing to CIBP pathogenesis, whole proteins from the ipsilateral lumbar spinal cord of CIBP rats were extracted and analyzed using label free Liquid Chromatography with tandem mass spectrometry (LC-MS-MS). 422 DEPs, consisting of 167 up-regulated and 255 down-regulated proteins, were identified among total 1539 proteins. Gene Ontology (GO) enrichment analysis indicated that the DEPs were mainly involved in catabolic process, synaptic function, and enzymic activity. Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis indicated a series of pathways, including nervous system disease, hormonal signaling pathways and amino acid metabolism, were involved. STRING (Search Tool for the Retrieval of Interacting Genes/protein) analysis revealed a protein-protein interaction network for DEPs. Expression change of synaptic and mitochondrial related protein, such as complexin 1 (CPLX1), synaptosomal-associated protein 25 (SNAP25), synaptotagmin 1 (SYT1), aldehyde dehydrogenase isoform 1B1 (ALDH1B1), Glycine amidinotransferase (GATM) and NADH:ubiquinone oxidoreductase subunit A11 (NDUFA11), were further validated using immunofluorescence and Western blot analysis. This study provides valuable information for understanding the mechanisms of CIBP, and supplies potential therapeutic targets for cancer pain.